The Hermeneutics of power colonial discourses in the christian conversion of Kabicolan (1600-1859) - Gerona, Danilo Madrid (2005)
Confined within the regional of Kabikolan, this study examines the history of the establishment and development of the catholic missions undertaken by the Franciscans from 1600 until 1850. The system of Reducciuon, as the missionaries referred to their method of conversion, required not only the acceptance of the Catholic faith but a comprehensive transformation of the native culture. Christianization was thus intimately bound with Hispanization. Seen in this perspective, the successful imposition of Spanish colonialization was mainly attributed to the missionary efforts. Thus, the narrative of Catholic conversion of Kabikolan offers a new perspective for exploring the dynamics of power transactions beyond the bureaucratic and institutional domains of the colonial affairs. At the helm of this transaction were the small bands of Franciscans who secured their missionary mandate in the region when they landed in the coast of the region in 1578. Braving the dangers posed by the hostile terrain and native inhabitants, these few missionaries blazed new trails to expand the ambit of colonial hegemony. Armed only with their zeal and heroic faith, these friars laid down the groundwork for the establishment of the colonial order, oftentimes without the support of the regimes' coercive mechanisms. How did such a small band of friars, thinly scattered in a vast territory, succeed not only in installing the structural base of the colonial system but also in preserving the unwavering submission of the natives to Spain for more than three hundred years?The answers lie in the conversion strategy employed by the Franciscans. The role played by the friars in mitigating the abuses committed by the imperial agents on the natives significantly altered the otherwise adverse response of the colonial subjects to the regime. The manifest opposition ofthe friars to the brutality of the conquistadores and rapacity of the bureaucrats on the hapless population made the friars the benign representative of colonialism. In the pueblo, the Padre was the exclusive representative of the sovereign and paternal authorities of the imperial and celestial majesties: the Spanish King and the Christian God. By arrogating to himself the authorities of "Both Majesties", the friar was assured a vast arsenal of secular powers and limitless discursive resources enabling him to enshroud his secular conducts with transcendental implications. Legitimized by their spiritual discrourse, the Franciscans inconspicuously reconstituted the fundamental clusters of native society: sexuality, social identity, ethnicity and geography, system of governance, myths and other cultural practices. The absence of a consolidated and hostile resistance to the friars for more than three hundred years clearly speak of the triumph of colonial rule achieved under the spiritual canopy of the Franciscan missionary endeavors.
"March 2005."
Thesis (Ph.D. Philippines Studies)--University of the Philippines Diliman.
Keywords: Conversion -- Christianity -- 1600-1850. -- Philippines -- Bicol; Franciscan -- Church history -- 18th century; Catholic church -- Franciscan history -- 17th century. -- Philippines; Hermeneutics -- Religious aspects -- Catholic church; Hermeneutics